Targeted Molecular Sequencing of Recurrent and Multifocal Non–HPV-associated Squamous Cell Carcinoma of the Vulva. (July 2021) - Pors, Jennifer; Tessier-Cloutier, Basile; Thompson, Emily; Almadani, Noorah; Ho, Julie; Gilks, Blake; Huntsman, David; Hoang, Lynn
Abstract : Recurrent vulvar squamous cell carcinomas (SCCs) are a poorly understood and aggressive group of treatment-resistant neoplasms. Currently, it remains unclear whether these are in fact recurrences of the same primary tumor, or the development of entirely new tumors. Here, to address this question, we examined the mutational profile of a series of patients with recurrent or multifocal non–human papilloma virus (HPV)-associated vulvar SCC. We performed a targeted 33-gene next-generation sequencing panel on a series of 14 patients with recurrent or multifocal non–HPV-associated vulvar SCC and precursor neoplasms. This amounted to 54 cases (33 SCC, 1 verrucous carcinoma, 13 differentiated vulvar intraepithelial neoplasia, and 7 differentiated exophytic vulvar intraepithelial lesion), with 79 mutations detected altogether. TP53 [51/79 (65%)] was the most frequently mutated gene. Mutations in PIK3CA [16/79 (20%)), HRAS [6/79 (8%)], PTEN [4/79 (5%)], EGFR [1/79 (1%)], and GNAS [1/79 (1%)] were occasionally seen. Most patients with SCC [5/9 (56%)] recurrent, 4/5 (80%) multifocal] demonstrated a clonal relationship, and harbored the same mutations in the same genes in metachronous or synchronous tumors. A subset of the recurrent tumors [2/5 (40%)] recurred with additional mutations. These clonal relationships were shared between SCC and differentiated vulvar intraepithelial neoplasia in each case. By contrast, a small number of recurrent tumors [3/9 (33%)] demonstrated novel mutations, entirely different from the primary tumor. Thus, our findings suggest that recurrent non–HPV-associated vulvar SCC can arise from 2 mechanisms.